2021
DOI: 10.5005/jp-journals-10005-2068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Shear Bond Strength of Composites to the Sodium Ascorbate Hydrogel-treated Bleached Enamel Surfaces: An In Vitro Analysis

Abstract: A bstract Aim To compare the shear bond strength of composites to the sodium ascorbate hydrogel-treated bleached enamel surfaces. Materials and methods Sixty-six extracted human maxillary first premolars were sectioned mesiodistally to obtain two nonocclusal surfaces ( n = 132). The specimen in the experimental group ( n = 80) were divided into four treatment groups depending upon bleaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…The use of antioxidants in dentistry is not new. Sodium ascorbate is frequently used before the bonding procedure after tooth bleaching [23][24][25][26]. Rodríguez-Barragué et al [27], through a systematic review and meta-analysis of in vitro studies, investigated the effects of antioxidants on the bond strength of composite resins to bleached enamel and found that the application of 10% SA for 1 min was effective in increasing the bond strength [27].…”
Section: Discussionmentioning
confidence: 99%
“…The use of antioxidants in dentistry is not new. Sodium ascorbate is frequently used before the bonding procedure after tooth bleaching [23][24][25][26]. Rodríguez-Barragué et al [27], through a systematic review and meta-analysis of in vitro studies, investigated the effects of antioxidants on the bond strength of composite resins to bleached enamel and found that the application of 10% SA for 1 min was effective in increasing the bond strength [27].…”
Section: Discussionmentioning
confidence: 99%